Concussion in adolescence and risk of multiple sclerosis. Issue 4 (25th September 2017) - Montgomery, Scott; Hiyoshi, Ayako; Burkill, Sarah; Alfredsson, Lars; Bahmanyar, Shahram; Olsson, Tomas
Abstract : Objective: To assess whether concussion in childhood or adolescence is associated with subsequent multiple sclerosis (MS) risk. Previous research suggests an association, but methodological limitations included retrospective data collection and small study populations. Methods: The national Swedish Patient Register (hospital diagnoses) and MS Register were used to identify all MS diagnoses up to 2012 among people born since 1964, when the Patient Register was established. The 7, 292 patients with MS were matched individually with 10 people without MS by sex, year of birth, age/vital status at MS diagnosis, and region of residence (county), resulting in a study population of 80, 212. Diagnoses of concussion and control diagnoses of broken limb bones were identified using the Patient Register from birth to age 10 years or from age 11 to 20 years. Conditional logistic regression was used to examine associations with MS. Results: Concussion in adolescence was associated with a raised risk of MS, producing adjusted odds ratios (95% confidence intervals) of 1.22 (1.05–1.42, p = 0.008) and 2.33 (1.35–4.04, p = 0.002) for 1 diagnosis of concussion and >1 diagnosis of concussion, respectively, compared with none. No notable association with MS was observed for concussion in childhood, or broken limb bones in childhood and adolescence. Interpretation: Head trauma in adolescence, particularly if repeated, is associated with a raised risk of future MS, possibly due to initiation of an autoimmune process in the central nervous system. This further emphasizes the importance of protecting young people from head injuries. Ann Neurol 2017;82:554–561